The Influence of Leadership Style and Organizational Culture on Employee Performance with Employee Motivation as a Moderating Variable in BPJS Employment Kisaran Branch and Padang Sidimpuan Branch - Erwin Veri Siregar; Muhammad Isa Indrawan (Lafadz Jaya Publisher, 2025)
Employee performance is a major factor in the success of an organization, including BPJS Employment. This study aims to analyze the influence of leadership style and organizational culture on employee performance, with motivation as a moderating variable. The research method used is a quantitative approach with data collection techniques through questionnaire surveys distributed to BPJS Employment employees at the Kisaran Branch and Padang Sidempuan Branch. Data analysis was carried out using regression methods and moderation tests to determine the relationship between variables. The results of the study indicate that leadership style has a significant influence on employee performance. A strong organizational culture also contributes to increasing employee productivity and loyalty. In addition, employee motivation has been shown to moderate the relationship between leadership style and organizational culture on performance, where high motivation strengthens the positive impact of leadership and organizational culture on employee performance. The implication of this study is the importance of leaders in implementing an appropriate leadership style and building a positive organizational culture in order to improve employee performance. BPJS Employment is advised to develop leadership training programs, strengthen a productive work culture, and provide incentives that can increase employee motivation.